Caminar - Brown, Skila (Somerville, Massachusetts : Candlewick Press, 2014)
Carlos knows that when the soldiers arrive with warnings about the Communist rebels, it is time to be a man and defend the village, keep everyone safe. But Mama tells him not yet -- he's still her quiet moonfaced boy. The soldiers laugh at the villagers, and before they move on, a neighbor is found dangling from a tree, a sign on his neck: Communist. Mama tells Carlos to run and hide, then try to find her ... Numb and alone, he must join a band of guerillas as they trek to the top of the mountain where Carlos's abuela lives. Will he be in time, and brave enough, to warn them about the soldiers? What will he do then? A novel in verse inspired by actual events during Guatemala's civil war, Caminar is the moving story of a boy who loses nearly everything before discovering who he really is.--Amazon.
Keywords: Guatemala -- History -- Civil War, 1960-1996 -- Juvenile fiction; Guatemala -- History -- Civil War, 1960-1996 -- Fiction; Novels in verse